PROSPECTS FOR THE DEVELOPMENT OF MATHEMATICS IN THE GREEN ECONOMY - Karshiboyev , Shuhrat; Sattarova , Madina Isoqulovna (Scientific practical conference, 2025)
This article explores the critical role of mathematics in advancing the green economy across Central Asian countries—Kazakhstan, Uzbekistan, Kyrgyzstan, Tajikistan, and Turkmenistan. Emphasizing that mathematics remains indispensable in areas such as renewable energy optimization, climate modeling, and economic forecasting, the article highlights how mathematical tools support sustainable policy design and energy infrastructure planning. It analyzes recent statistical data and historical developments while referencing global and regional best practices. The article also discusses educational reforms in Central Asia that aim to build the mathematical capacity needed for a green transition. The analysis concludes that fostering mathematical education and research is essential to achieving long-term environmental and economic resilience in the region.